2010
DOI: 10.1088/0004-637x/716/1/866
|View full text |Cite
|
Sign up to set email alerts
|

A SEARCH FOR BINARY ACTIVE GALACTIC NUCLEI: DOUBLE-PEAKED [O III] AGNs IN THE SLOAN DIGITAL SKY SURVEY

Abstract: We present AGN from the Sloan Digital Sky Survey (SDSS) having doublepeaked profiles of [O iii] λλ 5007, 4959 and other narrow emission-lines, motivated by the prospect of finding candidate binary AGN. These objects were identified by means of a visual examination of 21,592 quasars at z < 0.7 in SDSS Data Release 7 (DR7). Of the spectra with adequate signal-to-noise, 148 spectra exhibit a double-peaked [O iii] profile. Of these, 86 are Type 1 AGN and 62 are Type 2 AGN. Only two give the appearance of possibly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
253
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(262 citation statements)
references
References 34 publications
8
253
1
Order By: Relevance
“…For the former statement to hold, they had to assume identical bolometric corrections and Eddington ratios for both components in each binary system. For the subsample where systemic redshifts could be measured from stellar absorption lines (compiled from Wang et al 2009;Liu et al 2010b;Smith et al 2010), we found that both merging and isolated double-peaked AGNs fall on the same anti-correlation with similar dispersions (Figure 5). Because the isolated double-peaked AGNs cannot be kpc-scale binary AGNs, these results show that other mechanisms, such as jetdriven outflows, extended emission-line nebulae, and peculiar kinematics in the narrow-line regions, can produce the same double-peaked line profiles and the apparent virial relation of Wang et al (2009).…”
Section: Isolated Double-peaked Agnsmentioning
confidence: 70%
See 3 more Smart Citations
“…For the former statement to hold, they had to assume identical bolometric corrections and Eddington ratios for both components in each binary system. For the subsample where systemic redshifts could be measured from stellar absorption lines (compiled from Wang et al 2009;Liu et al 2010b;Smith et al 2010), we found that both merging and isolated double-peaked AGNs fall on the same anti-correlation with similar dispersions (Figure 5). Because the isolated double-peaked AGNs cannot be kpc-scale binary AGNs, these results show that other mechanisms, such as jetdriven outflows, extended emission-line nebulae, and peculiar kinematics in the narrow-line regions, can produce the same double-peaked line profiles and the apparent virial relation of Wang et al (2009).…”
Section: Isolated Double-peaked Agnsmentioning
confidence: 70%
“…Confirmation of three of the type-2 binary systems (1108+0659, 1146+5110, and 1332+0606) with seeing-limited imaging and long-slit spectroscopy previously appeared in Liu et al (2010a). Smith et al (2010) also noticed the unusual morphologies of 1157+0816 and 1307+4604 in the SDSS images. (A color version of this figure is available in the online journal.)…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…It has been suspected that double-peaked AGNs, for example, those that have double-peaked [O III] lines, are binary AGN candidates. There have been extensive works on the properties of double-peaked AGNs (Wang et al 2009;Smith et al 2010;Shen et al 2011). Although some double-peaked AGNs are indeed binary AGNs, it turns out that this method is not very efficient.…”
Section: Introductionmentioning
confidence: 99%